2013
DOI: 10.1172/jci64782
|View full text |Cite
|
Sign up to set email alerts
|

Loss of SPARC in bladder cancer enhances carcinogenesis and progression

Abstract: Secreted protein acidic and rich in cysteine (SPARC) has been implicated in multiple aspects of human cancer. However, its role in bladder carcinogenesis and metastasis are unclear,with some studies suggesting it may be a promoter and others arguing the opposite. Using a chemical carcinogenesis model in Sparc-deficient mice and their wild-type littermates, we found that loss of SPARC accelerated the development of urothelial preneoplasia (atypia and dysplasia), neoplasia, and metastasis and was associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
89
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(97 citation statements)
references
References 68 publications
8
89
0
Order By: Relevance
“…Further work on the consequences of loss of RHOGDI2 expression implicated endothelin 1 (EDN1) and versican (VCAN) as promoters of an inflammatory environment involving macrophages and the chemokine (C-C motif) ligand 2 (CCL2)-chemokine (C-C motif) receptor 2 (CCR2) signalling axis that is permissive for metastasis 177 178 . A similar relationship of loss of secreted protein acidic and rich in cysteine (SPARC) with metastasis and regulation of inflammatory response in bladder cancer has been reported 179 . Reduced expression of activating transcription factor 3 (ATF3), also a regulator of inflammation, has been implicated in driving metastasis through transcriptional regulation of gelsolinmediated actin re-modelling.…”
Section: Emt and Metastasissupporting
confidence: 64%
“…Further work on the consequences of loss of RHOGDI2 expression implicated endothelin 1 (EDN1) and versican (VCAN) as promoters of an inflammatory environment involving macrophages and the chemokine (C-C motif) ligand 2 (CCL2)-chemokine (C-C motif) receptor 2 (CCR2) signalling axis that is permissive for metastasis 177 178 . A similar relationship of loss of secreted protein acidic and rich in cysteine (SPARC) with metastasis and regulation of inflammatory response in bladder cancer has been reported 179 . Reduced expression of activating transcription factor 3 (ATF3), also a regulator of inflammation, has been implicated in driving metastasis through transcriptional regulation of gelsolinmediated actin re-modelling.…”
Section: Emt and Metastasissupporting
confidence: 64%
“…SPARC plays a significant role in tissue remodeling, maintaining cell matrix integrity and interaction and collagen fiber assembly (34). Stroma-as well as tumor-secreted SPARC is known to affect tumor growth in cell type-and context-dependent manners by regu- lating cell proliferation, adhesion, migration, invasion, and angiogenesis (25,(35)(36)(37)(38). In prostate cancer, apparent conflicting results regarding SPARC expression in both clinical and experimental studies suggest that the role of SPARC is even more complex.…”
Section: Discussionmentioning
confidence: 99%
“…Src interacts with and phosphorylates RhoGDI2 to enhance the metastasis suppressive effects [109]. Recently, Said et al showed that RhoGDI2-deficient disseminated tumor cells secrete several soluble factors (i.e., ECM molecules, versican, CCL2 and IL6) that stimulate macrophage recruitment [110][111][112]. The resulting 'inflammation storm' induces formation of a pulmonary pre-metastatic niche.…”
Section: Rhogdi2mentioning
confidence: 99%